Analisis prediksi financial distress menggunakan arus kas operasi dan corporate governance pada perusahaan sektor infrastruktur yang terdaftar di Bursa Efek Indonesia tahun 2019-2023 - Adelia Andjani Putri Nawanto (Universitas Negeri Surabaya, 2025)
Competition among companies forces company management to manage finance and corporate governance well in order to avoid the risk of bankruptcy. This study aims to determine the impact of operating cash flow on current liability, operating cash flow on net income, proportion of independent commissioners, the size of board of directors, the size of audit committee, institutional ownership, and management ownership on the likelihood of financial distress in the infrastructure sector during the period from 2019 to 2023. The population in this study includes 67 infrastructure sector companies listed on the Indonesia Stock Exchange (IDX). The sample used consists of 33 companies, with a purposive sampling method. The data obtained were analyzed using Stata 17 software with logistic regression analysis. The results of the study indicate that institutional ownership and management ownership have a negative effect on the likelihood of financial distress. Meanwhile, operating cash flow to current liabilities, operating cash flow to net income, independent commissioners, the size of the board of directors, and the size of the audit committee do not affect the likelihood of financial difficulties. Therefore, infrastructure sector companies are advised to pay attention to institutional ownership and management ownership, as both factors influence the likelihood of financial distress. This is due to the monitoring capabilities of institutions and management over the company, enabling them to make appropriate decisions and reduce the risk of financial distress.